Chronic post-traumatic pain: rheumatological and orthopedic aspects - A. E. Karateev; V. A. Nesterenko; M. A. Makarov; A. M. Lila (Научно-практическая ревматология)
Trauma causes a complex local and systemic reaction of the macroorganism, the consequences of which can be various functional, neurological and psychoemotional disorders. One of the most painful complications of injuries of the musculoskeletal system is chronic post-traumatic pain (CPTP), which occurs, depending on the severity of the damage, in 10–50% of cases. The pathogenesis of this syndrome is multifactorial and includes the development of chronic inflammation, degenerative changes (fibrosis, angiogenesis, heterotopic ossification), pathology of the muscular and nervous systems, neuroplastic changes leading to the development of central sensitization, as well as depression, anxiety and catastrophization. Risk factors for CPTP should be considered the severity of injury, comorbid diseases and conditions (in particular, obesity), stress and serious trauma-related experiences (within the framework of post-traumatic stress disorder), the development of post-traumatic osteoarthritis and chronic tendopathy, genetic predisposition, deficiencies in treatment and rehabilitation in the early period after injury. To date, there is no clear system of prevention and treatment of CPTP. Considering the pathogenesis of this suffering, adequate anesthesia after injury, active anti–inflammatory therapy (including local injections of glucocorticoids), the use of hyaluronic acid, slow-acting symptomatic agents and autologous cellular preparations – platelet-riched plasma, mesenchymal stem cells, etc. are of fundamental importance. However, therapeutic and surgical methods of CPTP control require further study